Entomological art: engaging science and community / Zulfadhli Mahfodz and Zaidatul Shakila Mohamad Ashari - Mahfodz, Zulfadhli; Mohamad Ashari, Zaidatul Shakila (2022)
Entomology is a branch of science that specifi-cally dealing with insects. Insects are dominant group of animals on Earth today among other terrestrial animals. They are well adapted to any kind of habitat and thus can be found everywhere (Triplehorn & Johnson, 2005). Insects and hu-mans have had a long-standing and close relation-ship. Some people see insects as nuisance, rather than as beneficial creatures and serve many eco-system services. We will continue to rely on and be inspired by insects because of their diversity, abundance, ecological benefits, and cultural links (Leather, 2015; Duffus et al., 2021).